Anlotinib Inhibits PFKFB3-Driven Glycolysis in Myofibroblasts to Reverse Pulmonary Fibrosis - Chen, Weimou; Zhang, Jinming; Zhong, Wenshan; Liu, Yuanyuan; Lu, Ye; Zeng, Zhaojin; Huang, Haohua; Wan, Xuan; Meng, Xiaojing; Zou, Fei; Cai, Shaoxi; Dong, Hangming (Frontiers in Pharmacology, 2021)
Idiopathic pulmonary fibrosis (IPF) is a fatal disease in which the normal alveolar network is gradually replaced by fibrotic scars. Current evidence suggests that metabolic alterations correlate with myofibroblast activation in IPF. Anlotinib has been proposed to have antifibrotic effects, but the efficacy and mechanisms of anlotinib against lung fibrosis have not been systematically evaluated. The antifibrotic effects of anlotinib were evaluated in bleomycin-induced mouse models and transforming growth factor-beta 1 (TGF-β1)-stimulated lung fibroblasts. We measured lactate levels, 2-NBDG glucose uptake and the extracellular acidification rate (ECAR) to assess glycolysis in fibroblasts. RNA-protein coimmunoprecipitation (RIP) and polysome analyses were performed to investigate novel mechanisms of glycolytic reprogramming in pulmonary fibrosis. We found that anlotinib diminished myofibroblast activation and inhibited the augmentation of glycolysis. Moreover, we show that PCBP3 posttranscriptionally increases PFKFB3 expression by promoting its translation during myofibroblast activation, thus promoting glycolysis in myofibroblasts. Regarding mechanism, anlotinib exerts potent antifibrotic effects by downregulating PCBP3, reducing PFKFB3 translation and inhibiting glycolysis in myofibroblasts. Furthermore, we observed that anlotinib had preventative and therapeutic antifibrotic effects on bleomycin-induced pulmonary fibrosis. Therefore, we identify PCBP3 as a protein involved in the regulation of glycolysis reprogramming and lung fibrogenesis and propose it as a therapeutic target for pulmonary fibrosis. Our data suggest that anlotinib has antifibrotic effects on the lungs, and we provide a novel mechanism for this effect. Anlotinib may constitute a novel and potent candidate for the treatment of pulmonary fibrosis.